Safety and feasibility of dual antiplatelet therapy termination guided by angioscopic findings 6 months after flow diverter placement - Fukutome, Kenji; Aketa, Shuta; Fukumori, Junji; Fujita, Taigi; Fukunaga, Motoki; Shiraishi, Yuki; Shimotsuma, Atsuko; Murakami, Yasutaka; Matsuoka, Ryuta; Shiba, Mikio; Tei, Rinsei; Shin, Yasushi; et al. (Frontiers in Neurology, 2025)
BackgroundFlow diverters (FDs) are commonly used to treat intracranial aneurysms with wide necks. Dual antiplatelet therapy (DAPT) is essential during the perioperative period to prevent thrombosis; however, it increases the risk of hemorrhagic complications, warranting early discontinuation when feasible. Neointimal formation over FD is crucial for safe DAPT discontinuation. This study aimed to directly visualize neointimal coverage 6 months after FD placement using angioscopy and evaluate the safety of DAPT termination.MethodsEight consecutive patients undergoing FD placement for internal carotid artery aneurysms between April 2022 and February 2024 were included in the prospective evaluation. Angioscopy was conducted at 6 months (±1 month) after FD placement to assess neointimal formation, which was graded 0–3 based on coverage (grade 0: no neointima; grade 1: slight; grade 2: translucent coverage; grade 3: full opaque coverage). Cone-beam computed tomography (CT) was concurrently performed to evaluate radiolucent gaps as indirect evidence of neointima formation. DAPT was discontinued if the neointimal coverage was graded ≥1, followed by the monitoring of ischemic events for 1 month.ResultsThe mean age of patients was 60.5 (49–81) years, and the mean aneurysm diameter was 7.7 mm (5.1–14.6 mm). Angioscopic neointimal grading was ≥1 in all cases, while cone-beam CT revealed no radiolucent gaps in one case. No procedural complications were observed. Following DAPT discontinuation, all the patients were administered single antiplatelet therapy, with no ischemic events observed within 1 month.ConclusionAngioscopy reliably confirmed neointimal coverage 6 months after FD placement, suggesting the potential for safe DAPT discontinuation. The findings underscore the superiority of angioscopy over cone-beam CT in identifying thin neointima. Further studies involving larger cohorts and applying advanced imaging technologies are required to optimize post-FD antiplatelet therapy.